A first‐in‐man safety and pharmacokinetics study of nangibotide, a new modulator of innate immune response through TREM‐1 receptor inhibition. (20th July 2018) - Cuvier, Valerie; Lorch, Ulrike; Witte, Stephan; Olivier, Aurelie; Gibot, Sebastien; Delor, Isabelle; Garaud, Jean‐Jacques; Derive, Marc; Salcedo‐Magguilli, Margarita
Abstract : Aims: The peptide nangibotide is the first clinical‐stage agent targeting the immunoreceptor TREM‐1 (triggering receptor expressed on myeloid cells‐1) and is being investigated as a novel therapy for acute inflammatory disorders such as septic shock. This first‐in‐man, randomized, double‐blind, ascending dose, placebo‐controlled Phase I study evaluated the safety, tolerability and pharmacokinetics of nangibotide. Methods: Twenty‐seven healthy subjects (aged 18–45 years) were randomized into eight groups. Nangibotide was administered as a single continuous intravenous infusion. The first two groups received a single i.v. dose of 1 and 10 mg, respectively, over 15 min. Subsequent groups were randomized in a product : placebo ratio of 3:1 at doses ranging from 0.03 to 6 mg kg −1 h −1 over 7 h 45 min, preceded by a 15‐minute loading dose of up to 5 mg kg −1 . Results: Nangibotide was safe and well tolerated up to the highest dose tested. There were only few adverse events and they were mild in severity and considered unrelated to treatment. Nangibotide displayed dose‐proportional PK properties, with a clearance of 6.6 l kg −1 h −1 for a subject of 70 kg and a 3 min effective half‐life, which are compatible with extensive enzymatic metabolism in blood. Central and peripheral volumes of distribution were 16.7 l and 15.9 l respectively, indicating limited distribution of the drug mainly in blood and interstitial fluid. No circulating anti‐drug antibodies were detectable up to 28 days after administration. Conclusions: The novel immunomodulator nangibotide displayed favourable safety and PK profiles at all doses, including expected pharmacologically active doses, and warrants further clinical development.